EVALUATION OF EFFECT OF THYMOL COMBINED WITH LACTIC ACID OR SODIUM LACTATE ON PSYCHROPHILIC BACTERIA AND SALMONELLA SPP. ON CHICKEN DRUMSTICK - Ilhak, Osman Irfan; Incili, Gokhan Kursad; Durmusoglu, Halil (Walter de Gruyter Gmbh, 2017)
This study was carried out to evaluate the combined antimicrobial effect of thymol with lactic acid or sodium lactate on Salmonella and psychrophilic bacteria on chicken drumstick. Drumstick samples were artificially contaminated with Salmonella spp., then sprayed with sterile 0.85% NaCl solution (control), and thymol (0.25% w/v) with lactic acid (2% and 4% v/v) or sodium lactate (2% and 4% v/v), alone or in combination, for 30 s. The samples were stored at 4 degrees C and analyzed on days 0, 2 and 4 for Salmonella and psychrophilic bacteria. Thymol alone did not show antibacterial effect on Salmonella and psychrophilic bacteria on chicken drumstick when compared with the control group during storage period. Spray with 4% lactic acid + thymol reduced Salmonella and psychrophilic bacteria by 1.4 and 1.8 log(10) CFU/ml on day 0, respectively. A significant decrease in the number of Salmonella and psychrophilic bacteria was observed in the samples sprayed with 4% lactic acid and 4% lactic acid + thymol on days 2 and 4 when compared to the control (P<0.05). The combinations of thymol with lactic acid or sodium lactate did not show synergistic or additive effect on Salmonella and psychrophilic bacteria present on chicken drumstick with skin.
Keywords: chicken drumstick; thymol; lactic acid; Salmonella; psychrophilic bacteria